2019
DOI: 10.1111/ijpo.12557
|View full text |Cite
|
Sign up to set email alerts
|

The cross‐sectional and prospective associations between sleep characteristics and adiposity in toddlers: Results from the GET UP! Study

Abstract: Summary Background The associations between sleep characteristics and adiposity in children under three years are not fully understood yet. Objective The objective of the study is to examine the cross‐sectional and prospective associations between sleep characteristics and adiposity in toddlers over a 12‐month period. Methods Participants were 202 toddlers from the GET‐UP! Study. Sleep duration, sleep timing, and sleep variability were assessed using 24‐hour accelerometry for seven consecutive days. Height and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…We did not find a significant association with weight status and bedtime in this sample, which is consistent with some studies [ 10 , 25 ], but not others [ 33 , 34 , 35 ]. This discrepancy can be partially explained by the various assessments of sleep timing, diverse measurements and definitions of weight status, confounding factors in the model, and different sample size in analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find a significant association with weight status and bedtime in this sample, which is consistent with some studies [ 10 , 25 ], but not others [ 33 , 34 , 35 ]. This discrepancy can be partially explained by the various assessments of sleep timing, diverse measurements and definitions of weight status, confounding factors in the model, and different sample size in analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Previous epidemiological studies regarding waking up time and weight status were limited and their results varied across different population groups. No significant association was found in healthy adults [ 24 ] and toddlers aged 12 to 26 months [ 25 ]. A cross-sectional study in adults with intellectual deficiency reported significantly higher odds of obesity in the late-rise group, compared with early-rise group [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies [26,33], accelerometry data were visually inspected minute by minute, in consultation with the activity logs, to identify nap and nighttime sleep duration. Specifically, the nap onset/bedtime was initially located when a switch in the accelerometer output from the inclinometer sitting or standing to inclinometer lying or off was detected, which approximately corresponded with the nap onset registered in the corresponding activity log.…”
Section: Physical Activity Sedentary Behaviour and Sleepmentioning
confidence: 99%
“…Sleep problems are common in children and adolescents with obesity, and have an impact on pediatric obesity 1‐4 . Obstructive sleep apnea (OSA) is one of sleep problems characterised by repeated partial or complete collapse of the upper airway during sleep, causing chronic intermittent hypoxia (CIH) and sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%